AI-Assisted Design Concept Exploration Through Character Space Construction - Sano, Shin; Yamada, Seiji (Frontiers in Psychology, 2022)
We propose an AI-assisted design concept exploration tool, the ``Character Space Construction'' (``CSC''). Concept designers explore and articulate the target product aesthetics and semantics in language, which is expressed using ``Design Concept Phrases'' (``DCPs''), that is, compound adjective phrases, and contrasting terms that convey what are not their target design concepts. Designers often utilize this dichotomy technique to communicate the nature of their aesthetic and semantic design concepts with stakeholders, especially in an early design development phase. The CSC assists this designers' cognitive activity by constructing a ``Character Space'' (``CS''), which is a semantic quadrant system, in a structured manner. A CS created by designers with the assistance of the CSC enables them to discern and explain their design concepts in contrast with opposing terms. These terms in a CS are retrieved and combined in the CSC by using a knowledge graph. The CSC presents terms and phrases as lists of candidates to users from which users will choose in order to define the target design concept, which is then visualized in a CS. The participants in our experiment, who were in the ``arts and design'' profession, were given two conditions under which to create DCPs and explain them. One group created and explained the DCPs with the assistance of the proposed CSC, and the other did the same task without this assistance, given the freedom to use any publicly available web search tools instead. The result showed that the group assisted by the CSC indicated their tasks were supported significantly better, especially in exploration, as measured by the Creativity Support Index (CSI).